Factors of educational re-engagement in the trajectory of five Andalusian women - Picazo-Gutiérrez, Marina; Ruíz Bejarano, Aurora María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The results presented here are part of the project “Riesgo de fracaso y abandono escolar en Secundaria Obligatoria. Educational, family and sociocultural contexts. A qualitative study” (Code: SEJ 2664) and aims to analyze and understand in Andalusia what factors determine that students who have been at risk and / or dropout in ESO resume their studies and re-enter the education system. All this is done from the voice of the protagonists themselves, putting them at the center of the research in order to approach their reality; lived and perceived in an individual and particular way.